2006
DOI: 10.1017/s1355617706060644
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reward and punishment contingencies on decision-making in multiple sclerosis

Abstract: Many patients with multiple sclerosis (MS) show cognitive and emotional disorders. The purpose of this study is to evaluate the role of contingency learning in decision-making in young, non-depressed, highly functioning patients with MS (n 5 21) and in matched healthy controls (n 5 30). Executive functions, attention, short-term memory, speed of information processing, and selection and retrieval of linguistic material were also investigated. Contingency learning based on the cumulative effect of reward and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 33 publications
5
48
1
2
Order By: Relevance
“…Our main finding is that, in such an early MS population, the ability to learn to avoid disadvantageous decks in the IGT does not differ from that of controls and that, in contrast to more advanced MS [22], decision making seems to be preserved in the early stages of the disease. Our results differ from those of Nagy et al [30] who found impaired decision making in MS patients with mild disability. For each boxplot, the middle horizontal line is the median, the bottom and top represent quartiles 1 and 3, the upper and lower bars mark the last observation at a distance of less than 1.5 times the interquartile range from the edge of the box, and the diamonds represent all observations that are outside the bars However, they tested a slightly more advanced MS population (all their patients already had definite MS and disease duration was one year longer on average) and the presence of IGT difficulties in their study group might be related to the evolution of the MS process.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our main finding is that, in such an early MS population, the ability to learn to avoid disadvantageous decks in the IGT does not differ from that of controls and that, in contrast to more advanced MS [22], decision making seems to be preserved in the early stages of the disease. Our results differ from those of Nagy et al [30] who found impaired decision making in MS patients with mild disability. For each boxplot, the middle horizontal line is the median, the bottom and top represent quartiles 1 and 3, the upper and lower bars mark the last observation at a distance of less than 1.5 times the interquartile range from the edge of the box, and the diamonds represent all observations that are outside the bars However, they tested a slightly more advanced MS population (all their patients already had definite MS and disease duration was one year longer on average) and the presence of IGT difficulties in their study group might be related to the evolution of the MS process.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Maia & McLelland [26], consciously accessible knowledge may induce overt behavior and verbal reports, which influence directly decision making; the use of non-conscious somatic markers may not be necessary in that context. For Nagy et al [30], poor decision making was rather the consequence of an impaired learning process across trials and of a greater sensitivity to recent outcomes, independently of gains or losses. Finally, we have previously suggested an impairment of emotional experience instead of cognitive changes as an inducing mechanism [22].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Such as Nagy et al ( 2006) , we could not relate dysfunction in the IGT to executive defi cits or to general cognitive impairment. In addition, decline in IGT performances occurred independently of MS course (i.e., sustained progression in disability or relapsing rate during Table 2.…”
Section: Discussionmentioning
confidence: 83%